Sustainability of Biofuel Production from Oil Palm Biomass - Lee, Keat Teong; Ofori-Boateng, Cynthia (Green Energy and Technology,, 2013)
This book evaluates and discusses the main sustainability challenges encountered in the production of biofuel and bio-products from oil palm biomass. It starts off with the emphasis on oil palm production, oil palm products recovery and oil palm wastes utilization. The simultaneous production of these bio-products for sustainable development is discussed. This is followed by the key factors defining the sustainability of biofuel and bio-product production from oil palm biomass. The environmental issues including ecological, life cycle assessment and environmental impact assessment of oil palm plantation, milling and refining for the production of biofuels and bio-products are presented. Socio-economic and thermodynamic analysis of the production processes are also evaluated using various sustainability assessment tools such as exergy. Lastly, methods of improving biofuel production systems for sustainable development are highlighted.